STARETEGI PEMBELAJARAN PAI PADA PTAI - Dr. Mardyawati (Ash-Shahabah : Jurnal Pendidikan dan Studi Islam, 2016)
Purpose of Education at very influential in the implementation, dynamics, direction and implementation of education at a higher education, especially at the College of Islamic Religion (PTAI). Thus it is necessary PTAI depth critical evaluation, for the formulation and the concept is very determining educational goals of the institution's goals. In the end, the quality or the quality of the education is the foundation of conceptual philosophy of education which frees and able to prepare future generations to survive (survive) and successfully face the challenges of his time. The ultimate goal of learning a particular college is scored undergraduate PTAI skilled in the art that characterized and, coupled with the values ​​of Islam. These objectives would be achieved by managing the learning process in PTAI and one way to achieve that goal is to pack the lecture by incorporating the material into an Islamic education curriculum in PTAI. Thus, the learning process is not just a professor presenting lectures (courses) to students who menghusus in each department, but deliver the lecture material makes matter the religion of Islam as one of the basic theory in presenting the material. Students are no longer made passive but should be made the driving force of educational activities (generators). Given the purpose of education in the College of Islamic Religion which prepares students to be scholars who "is able to do something" and not only able to "theorize" in other words, can be a scholar who is not only skilled in the art but is expected to appear to have the characteristics inherent in such scholars namely Islamic scholars. Thus the need for strategies, methods, specific approaches for lecturers in the learning process to make undergraduate coupled with Islamic values. This paper attempts to put forward ideas for effective contribution to the learning process starts by seeking for becoming teachers (lecturers) PAI on PTAI.